Pengaruh Gaya Kepemimpinan Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Sekretariat DPRD Kabupaten Alor - Hethi Eriyanti Matingmabi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to determine the Effect of Style Leadership, Work Environment and Work Discipline on Employee Performance On Office Secretariat DPRD Regency Alor. Type study This is description quantitative. Sample taken by using saturated sampling technique. The sample in this study were 37 employees. Data retrieval tool Which used is observation, interview, And studies literature. Model analysis the data used to answer the hypothesis is multiple analysis, t test, F test with use tool help SPSS version 22 for windows. Test instrument research This used For measure level valid, reliable and the classic assumptions of the answers to the research questionnaire. By using tools help calculate SPSS version 22 For Windows . Based on the results of each validity test variables with pearson correlation values ≥ 0.3 then the results of the validity test for each variable declared valid. The results of the reliability test for each variable with a Crobatc Alpha value ≥ 0.6 then the results of the reliability test for each variable are declared reliable. Normality test results Shapiro-Wilk with sig. ≥ 0.05 then the test results are declared normal. Test results heteroscedasticity shows that the value of each independent variable is > 0.05 then study This No happen heteroscedasticity. Results test multicollinearity show that mark VIF > tolerance so study This No happen multicollinearity. The results of the linearity test between the dependent variable and the independent variable shows that the deviation from linearity value is > 0.05, so there is a relationship between dependent variable with independent variable. Method analysis Which used is technique analysis regression linear double. Results with the t test to answer the first, second, and third hypotheses, meanwhile multiple linear regression analysis simultaneously used the F test to find out hypothesis fourth that is For know Influence Style Leadership, Dan Work Environment Work Discipline Against Employee Performance in the Office Alor Regency DPRD Secretariat. Based on the calculation results of regression analysis linear double in a manner Partial And in a manner simultaneous obtained mark significance variable style leadership as big 0.000, variable environment Work as big 0.000, variable work discipline of 0.003 and the simultaneous effect of the value of the F test significance is as big 0.000 b , results testing test t And test F more small from alpha (0.05), so testing the hypothesis proposed in this study is as follows : there are influences of leadership style, work environment and work discipline To Performance Employee On Office DPRD Secretariat Alor Regency.